Effect of selected additives and y-irradiation on the physicho-chemical, microbial quality and aroma stability of cold-stored onion puree - Sadoughi, Navideh (2011)
A distinctive characteristic of onion is the presence of alliaceous odor which accounts for its use as food, salad, spice, condiment and medicine. Pureed onion is one of the most suitable food materials as a ready-to-use ingredient. In general, after one week of storage, not only the color of purred onion changes to brown,but also its odor becomes unpleasant and its microbial content increase to make it unusable. In this study, the effect of different doses of selected additives and y-irradiation, and their combination on the color, odor, and physico-chemical, and nutritional properties of cold stored onion puree was investigated. The effect on microbial count was also investigated. Different concentration of ascorbic acid, lactic acid and citric acid significantly affected the total color and physico-chemical properties of onion puree during storage at 4 ˚C. However, These Selected additives did not have any significant effect on other organic acids contents and odor. The most important role of these additives is keeping original color and enhancing acidity. Samples with (0.3-1.5%) ascorbic acid and (0.5-0.8%) citric acid keep original color, especially samples with 0.5 and 1% ascorbic acid is extremely near to fresh samples. Using 0.5% ascorbic acid as the best additive is more economical and improves the quality of puree onion and helps to stabilize physico-chemical properties of cold stored onion puree with less browning, and better visual quality than control sample.y-Irradiation at different doses (1, 2, 3, 5 and 7) has significant effects on the total color, odor and physico-chemical and microbial properties of cold stored onion puree. The pH, titratable acidity, organic acid and microbial content of onion puree was more stable at different doses of gamma. The most important role of y- irradiation was a remarkably reduction in microbial count without decreasing in nutritional properties such as organic acids. However, high doses of y-irradiation had a negative effect on color, flavor and appearance. But low doses of y-irradiation not only decrease microbial content but also can also keep the original flavor. y-irradiation at 2 kGy enhances microbial food safety while the original flavor and color is nearer to the control sample as compared to sample that irradiated at 3, 5 and 7 doses. Combination of these two treatments is most effective in preventing the growth of microbial content and obtaining a product with the origin color and stabilizing physico-chemical properties such as pungency and nutritional properties such as vitamin C and organic acids of cold stored onion puree. So this combination of treatment can improve shelf life of onion puree for one month at 4˚C, 3 weeks at 10 ˚C or less than 2 weeks at 27 ˚C.